2016
DOI: 10.1007/s00383-016-3985-z
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal gastrointestinal perforation in Japan: a nationwide survey

Abstract: The mortality rates for ELBW decreased from 62.8 % in the previous survey to 41.1 % by the time of this survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…Accordingly, in 2008 Lin and colleagues reported 15 cases and reviewed the literature, finding higher incidence of NGP among LBW babies (52%) in particular, in extremely LBW neonates, and suggested that premature infants are more prone to develop a spontaneous gastric perforation due to the immaturity of the gastric tissue ( 2 ). Similarly, in the survey from Sato et al ( 45 ), 11 out of 42 neonates with gastric perforation were ELWB. Prematurity may predispose to NGP through several factors, including defects of the gastric muscle wall (especially in immature tissues of preterm babies), lack of intestinal pacemaker cells, and lack of C-KIT mast cell ( 27 ).…”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, in 2008 Lin and colleagues reported 15 cases and reviewed the literature, finding higher incidence of NGP among LBW babies (52%) in particular, in extremely LBW neonates, and suggested that premature infants are more prone to develop a spontaneous gastric perforation due to the immaturity of the gastric tissue ( 2 ). Similarly, in the survey from Sato et al ( 45 ), 11 out of 42 neonates with gastric perforation were ELWB. Prematurity may predispose to NGP through several factors, including defects of the gastric muscle wall (especially in immature tissues of preterm babies), lack of intestinal pacemaker cells, and lack of C-KIT mast cell ( 27 ).…”
Section: Discussionmentioning
confidence: 75%
“…This review included 104 male (61.9%) and 64 female (38.1%); 72 preterm (57.1%) and 54 full-term (42.9%) neonates after 42 cases from the studies by Sato et al were excluded due to the unavailability of data on their gestational age. [ 19 ] The perforation locations included the greater curvature (n = 90; 73.8%), lesser curvature (n = 16; 13.1%), anterior wall (n = 11; 9.0%), and posterior wall (n = 5; 4.1%) after 3, 1, and 42 cases from the studies by Shashikumar et al, Kiesewetter et al, and Sato et al were excluded, respectively, due to the unavailability of data on the location of perforation. [ 11 , 14 , 19 ] Three cases in study of Rosser et al and 1 case in study of Amadeo et al, which the perforation was identified at fundus, were included into group of greater curvature for statistical analysis-based anatomical position.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the response rate of level III perinatal centers (77.6%) was high, considerably higher than those of other recent nationwide surveys in Japan, such as 70.7% in a survey of the need for human milk banking, 10 64% for clinical kernicterus in preterm infants, 28 62.3% for neonatal transportation practices, 29 and 57.7% for neonatal gastrointestinal perforation. 30 In addition, a total of 14,934 VLBWI admitted to the level III perinatal centers that completed our questionnaire accounted for 69.4% (14,934/21,518) of the VLBWI admitted to all perinatal centers responding to this survey. Another limitation of this study is that we did not assess data about feeding intolerance because it is difficult to uniformly evaluate feeding intolerance using a questionnaire.…”
Section: Discussionmentioning
confidence: 99%